2022
DOI: 10.3390/ph16010006
|View full text |Cite
|
Sign up to set email alerts
|

Possible Implication of Nrf2, PPAR-γ and MAPKs Signaling in the Protective Role of Mangiferin against Renal Ischemia/Reperfusion in Rats

Abstract: Mangiferin (Mang) is a known glucosylxanthone that has proven its shielding effect against ischemia/reperfusion (Is/R). However, its full underlying mechanistic perspective against renal Is/R induced lesions is not fully revealed. Consequently, the purpose of this study is to track further non-investigated modulatory signals of Mang against the renal Is/R model involving nuclear factor erythroid 2-related factor (Nrf)2/heme oxygenase (HO)-1, peroxisome proliferator-activated receptor (PPAR)-γ/nuclear factor (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…Mechanistically, mangiferin is known to elicit its antioxidant and anti-inflammatory effects by acting on a wide range of targets, including the nuclear factor erythroid 2-related factor (Nrf)2/heme oxygenase (HO)-1, peroxisome proliferator-activated receptor (PPAR)-γ/nuclear factor (NF)-κB, p38 mitogen-activated protein kinase (MAPK), c -Jun N -terminal kinase (JNK), AMP-activated protein kinase (AMPK), and NLR family pyrin domain containing 3 (NLRP3) inflammasome signalling pathways [ 48 , 49 ]. We postulate that these targets were engaged by mangiferin in this study and the isomer ceibinin could also have engaged some or all of these targets, although this remains to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistically, mangiferin is known to elicit its antioxidant and anti-inflammatory effects by acting on a wide range of targets, including the nuclear factor erythroid 2-related factor (Nrf)2/heme oxygenase (HO)-1, peroxisome proliferator-activated receptor (PPAR)-γ/nuclear factor (NF)-κB, p38 mitogen-activated protein kinase (MAPK), c -Jun N -terminal kinase (JNK), AMP-activated protein kinase (AMPK), and NLR family pyrin domain containing 3 (NLRP3) inflammasome signalling pathways [ 48 , 49 ]. We postulate that these targets were engaged by mangiferin in this study and the isomer ceibinin could also have engaged some or all of these targets, although this remains to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, biliverdin is converted into bilirubin, thereby exerting strong antioxidant action ( Yu et al ., 2018 ; Jenkins and Gouge, 2021 ). Recently, it has been reported that Nrf2-dependent activation of HO-1 in RPE cells contributes to protection against mitochondrial damage-mediated apoptosis caused by oxidative stress ( Clementi et al ., 2022 ; Park et al ., 2022 ), and the importance of the Nrf2/HO-1 axis as a mechanism for the antioxidant activity of mangiferin in numerous cell lines has been emphasized ( Saha et al ., 2016 ; Al-Saeedi, 2021 ; Gendy et al ., 2022 ; Zhou et al ., 2023 ). In this study, mangiferin not only increased the expression of Nrf2 protein but also its phosphorylation in ARPE-19 cells treated with H 2 O 2 , and they were expressed predominantly in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…(2023) , mangiferin reduced ROS levels and increased the levels of SOD and glutathione (GSH) in a Parkinson’s disease model, and was able to reduce oxidative stress by targeting the Nrf2 pathway. Mangiferin also protected ischemia/reperfusion-related events and helped restore hyperglycemia-induced impaired angiogenesis through Nrf2 signaling, which was associated with increased expression of heme oxygenase (HO)-1 ( Gendy et al ., 2022 ; Zhou et al ., 2023 ). HO-1 is one of the representative downstream regulators of Nrf2 and contributes to the maintenance of redox homeostasis through its metabolites ( Yu et al ., 2018 ; Jenkins and Gouge, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…As formerly described by Gendy et al, (2022) [ 85 ], 5 µm slices were sliced into positive charged slides, rehydrated, and heat-retrieved before being incubated with primary anti-TNF- and VEGF for the duration of the night (at a dilution of 1:100). Following washing, tissue sections were incubated for 30 min at room temperature with a 1:1000 dilution of an HRP-labeled secondary antibody before being blocked for endogenous peroxidases.…”
Section: Methodsmentioning
confidence: 99%